More Helmets Fewer Deaths: Motorcycle Helmet Legislation Impacts Traumatic Brain Injury-Related Mortality in Young Adults. Issue 6 (June 2017) - Hassan, Ahmed; Jokar, Tahereh Orouji; Rhee, Peter; Ibraheem, Kareem; Kulvatunyou, Narong; Anderson, Kathryn Tinsley; Gries, Lynn; Roward, Zachary Thomas; Joseph, Bellal
The aim of our study was to assess the impact of helmet legislations on the incidence and the mortality rate of motorcycle collision (MCC)-related traumatic brain injury (TBI) in young adult trauma patients. A 1-year (2011) retrospective analysis was performed of all patients under 21 years old with trauma-related hospitalization using the Nationwide Inpatient Sample database (representing 20% of all in-patient admissions). Patients with MCC were identified using E-codes. States were classified into three groups based on helmet legislations: universal age helmet legislation, <18 years helmet legislation, and <21 years helmet legislation. Outcome measures were the rates of TBI and mortality. Linear regression analysis was used to assess outcomes among the states. A total of 1, 165, 150 patients with trauma-related hospitalizations across 29 states were reviewed of which, 587 patients with MCC were included. Ten states had universal age legislation; 13 states had age <18 years legislation, and 6 states had age <21 years legislation. There was a lower incidence in the rate of TBI (P = 0.03) in states with universal helmet legislations compared with states with age-restricted helmet legislation. Universal helmet legislations lowered the rate of MCC-related TBI injures by a factor of 2.15 (β coefficient: 2.15; 95% confidence interval: 0.91–10.18; P = 0.04). States with age-restricted helmet legislations have a higher rate of traumatic brain injury and mortality compared with states with universal helmet legislations. Establishing universal helmet legislations across the states may provide a potential preventive strategy against traumatic brain injury.